2017
DOI: 10.1002/aur.1874
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive behavior in autism: Minimal clinically important differences on the Vineland‐II

Abstract: The Vineland Adaptive Behavior Scales (2nd edition; Vineland-II) is the most widely used scale for assessing day-to-day "adaptive" skills. Yet, it is unknown how much Vineland-II scores must change for those changes to be regarded as clinically significant. We pooled data from over 9,000 individuals with ASD to show that changes of 2-3.75 points on the Vineland-II Composite score represent the "minimal clinically-important difference." These estimates will help evaluate the benefits of potential new treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 63 publications
8
103
1
1
Order By: Relevance
“…This may indicate that IQ‐adaptive discrepancies become more pronounced with higher IQ, such that in high‐IQ individuals adaptive skills are less commensurate with cognitive abilities. Although these effects were modest and only significant at trend level, they are in line with another recent study [Chatham et al, ], suggesting that cognitive ability does not fully explain impairments in adaptive functioning in ASD, and particularly in higher‐ability individuals. It is also noteworthy that albeit significant due to the large sample studied, age had only a modest effect on adaptive scores.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This may indicate that IQ‐adaptive discrepancies become more pronounced with higher IQ, such that in high‐IQ individuals adaptive skills are less commensurate with cognitive abilities. Although these effects were modest and only significant at trend level, they are in line with another recent study [Chatham et al, ], suggesting that cognitive ability does not fully explain impairments in adaptive functioning in ASD, and particularly in higher‐ability individuals. It is also noteworthy that albeit significant due to the large sample studied, age had only a modest effect on adaptive scores.…”
Section: Discussionsupporting
confidence: 89%
“…In ASD there is wide heterogeneity in the level of functioning across these domains, which is partly linked to development and level of cognitive abilities [Szatmari et al, ; Bal, Kim, Cheong, & Lord, ; Chatham et al, ; Farmer, Swineford, Swedo, & Thurm, ]. Although higher intellectual functioning is typically associated with better adaptive functioning, adaptive behavior tends to be more impaired than what would be expected based on general intellectual and cognitive ability [Bölte & Poustka, ; Klin et al, ; Charman et al, ; Kanne et al, ; Mouga, Almeida, Café, Duque, & Oliveira, ; Chatham et al, ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They lagged behind typical individuals the most for socialization, then communication, and finally daily living skills. This rank of impairment for the Vineland domains is similar to that reported in the literature [Chatham et al, ; Yang et al, ] and was found at each step of the study. Overall, the entire group improved, but we identified two contrasting adaptive trajectories: ~80% of the sample followed a low‐growth trajectory (LG), whereas the rest followed a high‐growth trajectory (HG).…”
Section: Discussionsupporting
confidence: 88%
“…Similarily, the CARS contains a substantial proportion of “negative” symptoms (abilities for which the absence has a diagnostic value for autism) which is related to the Vineland Social Skills subsubscale. Moreover, this predictive association may not exist to the same extent for autistic people with high verbal IQ and no speech delay [Cederlund et al, ; Howlin et al, ], where it was found only for communication and daily living skills, but not social skills [Chatham et al, ; Freeman et al, ]. Second, the evaluation of IQ (due to possible underestimation), language, and adaptation measurements in autism should be improved.…”
Section: Discussionmentioning
confidence: 99%